2020
DOI: 10.18820/24150487/as27i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Housing poverty in developing countries: Challenges and implications for decent accommodation in Swedru, Ghana

Abstract: Adequate supply of housing remains a challenge in developing countries. This article assesses the extent of housing poverty in developing countries and its implication for decent accommodation1 in Swedru, Ghana. Using a cross-sectional survey design coupled with stratified and systematic sampling techniques, 1,161 household participants were selected. Questionnaires and interviews were used to collect raw data from 496 houses in 16 neighbourhoods in the Swedru Township, Ghana. Findings showed that the vast maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
(1 reference statement)
1
9
0
Order By: Relevance
“…In most Ghanaian homes, more than three people share a single room and that in itself does not pave way for social distancing. For example, Ofori (2020) has shown that adequate supply of housing remains a challenge in developing countries, especially Ghana. A room occupancy rate of 5.51 indicates that households are congested and a population of 4,603 accommodated in 496 housing units is evident.…”
Section: The Results In Tablementioning
confidence: 99%
“…In most Ghanaian homes, more than three people share a single room and that in itself does not pave way for social distancing. For example, Ofori (2020) has shown that adequate supply of housing remains a challenge in developing countries, especially Ghana. A room occupancy rate of 5.51 indicates that households are congested and a population of 4,603 accommodated in 496 housing units is evident.…”
Section: The Results In Tablementioning
confidence: 99%
“…Various typical studies in countries such as Nigeria (Adedire & Adegbile, 2018;Zunguzane, Smallwood & Emuze, 2012), Ghana (Ofori, 2020), and South Africa (Landman, Matsebe & Mmonwa, 2009) focus on user needs and expectations and play a part in determining the quality of residential environment and the performance of housing in general. Ibem et al (2012) revealed that, in Nigeria, Papua New Guinea and Ghana, respectively, residents were dissatisfied with the building features.…”
Section: Building Performance Evaluationmentioning
confidence: 99%
“…In Ghana, the vast majority of rental houses occupied by low-income renters are associated with a lack of basic housing infrastructure and have poor housing facilities (Ofori, 2020). Tenants are inconvenienced when facilities such as toilets, bathrooms, pipes, and kitchens are not available or are not located in the house (Amenyah & Fletcher, 2013: 39).…”
Section: Inadequate Facilities and Servicesmentioning
confidence: 99%
“…Due to financial difficulty, most of the low-income earners have become homeless, thus compelling them to opt for slums and squatter settlements as options in most of the cities and towns (Serageldin et al, 2003, cited in Danso-Wiredu & Midheme, 2017. It is also revealing to note that some low-income urban dwellers live in small-sized single rooms, with those from extremely poor economic status migrants either sharing or staying with friends or relatives (Yankson, 2012: 12;Ofori, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation